A review of property rights in outer space from a land management perspective. Issue 2 (10th July 2021) - de Vries, Walter Timo; Hugentobler, Urs
Abstract : Purpose: In light of the discussions on outer space property management, this conceptual review paper aims to discuss and evaluate if, when and under which conditions certain land management and property right frameworks can apply to allocate and/or restrict property rights in outer space. Design/methodology/approach: This paper applies a pragmatic review approach which seeks to better understand if and how the basic tenets of the land management frameworks could better shape and revise the challenges in outer space regulations. Findings: Despite the fact that regulatory guidelines on outer space rights are existing, the analysis shows that these lack a number of practical tools and measures aiming at intervening if stakeholders do not follow the rules. With the use of land management frameworks, it is possible to derive policy options for making the outer space management more practical and action-oriented, in particular for the removal of space debris. These include amongst others more attention for formulating global public restrictions in outer space, incorporating regulatory guidelines for accessing open space regimes, addressing responsiveness and robustness in adherence and compliance to regulations Research limitations/implications: Given the conceptual and discursive character of the paper, there are no specific empirical data, yet several recommendations for further research include expanding the boundary work between the land management and regulatory outer space domain. Practical implications: The insights derived from land management and real estate related property theories could potentially provide new starting points for (re)formulating the regulatory framework for outer space property discourses. Social implications: Interpreting the outer space regulations from known and practiced land management perspective helps to bridge the policy–society knowledge and necessity gap on outer space activities. Originality/value: The specific land management perspective and discursive analysis on outer space debris provide new options for devising and extending regulatory guidelines for assigning responsibilities on outer space debris and debris rights, restrictions and responsibilities.